Modulatory effects of vasoactive intestinal peptide on intestinal mucosal immunity and microbial community of weaned piglets challenged by an enterotoxigenic Escherichia coli (K88). - Chunlan Xu (Public Library of Science (PLoS), 2014)
Toll-like receptors (TLRs) recognize microbial pathogens and trigger immune response, but their regulation by neuropeptide-vasoactive intestinal peptide (VIP) in weaned piglets infected by enterotoxigenic Escherichia coli (ETEC) K88 remains unexplored. Therefore, the study was conducted to investigate its role using a model of early weaned piglets infected by ETEC K88. Male Duroc × Landrace × Yorkshire piglets (n = 24) were randomly divided into control, ETEC K88, VIP, and ETEC K88+VIP groups. On the first three days, ETEC K88 and ETEC K88+VIP groups were orally administrated with ETEC K88, other two groups were given sterile medium. Then each piglet from VIP and ETEC K88+VIP group received 10 nmol VIP intraperitoneally (i.p.) once daily, on day four and six. On the seventh day, the piglets were sacrificed. The results indicated that administration of VIP improved the growth performance, reduced diarrhea incidence of ETEC K88 challenged pigs, and mitigated the histopathological changes of intestine. Serum levels of IL-2, IL-6, IL-12p40, IFN-γ and TNF-α in the ETEC K88+ VIP group were significantly reduced compared with those in the ETEC group. VIP significantly increased IL-4, IL-10, TGF-β and S-IgA production compared with the ETEC K88 group. Besides, VIP could inhibit the expression of TLR2, TLR4, MyD88, NF-κB p65 and the phosphorylation of IκB-α, p-ERK, p-JNK, and p-38 induced by ETEC K88. Moreover, VIP could upregulate the expression of occludin in the ileum mucosa compared with the ETEC K88 group. Colon and caecum content bacterial richness and diversity were lower for pigs in the ETEC group than the unchallenged groups. These results demonstrate that VIP is beneficial for the maturation of the intestinal mucosal immune system and elicited local immunomodulatory activities. The TLR2/4-MyD88 mediated NF-κB and MAPK signaling pathway may be critical to the mechanism underlying the modulatory effect of VIP on intestinal mucosal immune function and bacterial community.